NAFTA- 12 lat funkcjonowania - Kowalik, Paweł (NAFTA-Twelve Years after its Foundation, 2008)
n January 2006 the North American Free Trade Agreement (NAFTA) celebrated its twelve anniversary. This article presents the effects of the agreement on employment, consumer prices, economic development and levels of trade in its three signatories: Canada, Mexico, and the United States. To measure and compare the effects of NAFTA, this study analyzes data from 1993 to 2005.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 12, s. 109-124